(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Studies are being carried out at Karmat Ali, University of Basra’s Agricultural Research Station, College of Agriculture which is at 47.80o longitude and 30.57o north latitude, a field experiment was done. In silty loam soil during the spring agricultural season2022, to study the path coefficient analysis, correlations, variances, and the degree of heritability for three genotypes (Al-Maha, IPA-5018, Bhooth-106) of corn crop Zea mays L. The experiment was applied according to the method of factorial experiments using randomized complete block design (RCBD) with three replications. The trait of 300 grains weight had the strongest direct positive genetic and phenotypic effect on grain yield, according to the analysis of genetic and phenotypic path coefficients amounted to 0.806 and 0.582, respectively, followed by the characteristic of grains number in corn cob, which had a direct positive genetic and phenotypic effect on grain yield, amounted to 0.164 and 0.308, respectively. The grain yield showed a positive and highly significant genetic and phenotypic correlation with the characteristics of the weight of 300 grains, the number of cobs in plant, and grains number in cob reached (0.912** and 0.934**) (0.479** and 0.815**) (0.846** and 0.897**) for attributes in succession. Variations in grain yield caused by genetic, environmental, and phenotypic factors recorded a variation of 0.1554, 0.00736, and 0.1627, respectively, with a broad-sense heritability average of 95.51%. The heritability average in the broad sense varied according to the different studied traits, and the plant height trait recorded a highest heritability average of 98.74 percent, while protein in grains trait recorded the lowest heritability average in the broad sense, amounting to 68.55%.